2019
DOI: 10.1037/cns0000203
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of implicit and explicit beliefs on food preferences.

Abstract: Memories can have consequences on people's eating behavior. In the current experiment, we examined the effect of belief versus recollection on food preferences and then investigated whether explicit belief (i.e., self-reported) or implicit belief (i.e., measured by an autobiographical implicit association test; aIAT) had a similar effect on food preferences. Participants (N = 163) were falsely told that they got sick after eating egg salad in their childhood and then received guided imagery to induce false bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Consistent with previous research on nonbelieved memories (Li et al, 2020; G. Mazzoni et al, 2010; Otgaar et al, 2019; Wang et al, 2017, 2019), false social feedback exerted a powerful effect in altering autobiographical belief. After being told that their memory was in fact incorrect, participants reduced the autobiographical beliefs of their experiences and made more errors identifying their game partners and actions in the second test.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with previous research on nonbelieved memories (Li et al, 2020; G. Mazzoni et al, 2010; Otgaar et al, 2019; Wang et al, 2017, 2019), false social feedback exerted a powerful effect in altering autobiographical belief. After being told that their memory was in fact incorrect, participants reduced the autobiographical beliefs of their experiences and made more errors identifying their game partners and actions in the second test.…”
Section: Discussionsupporting
confidence: 87%
“…This apparent contradiction was resolved by an examination of participants' explicit statements about whether they believed or remembered each of the fake stories at the end of the procedure. In line with previous research [49], the majority of persistent memories were thus identified as non-believed memories, suggesting that debriefing works well to reduce belief in a story, even if participants still retain the memory of it. Interestingly, these rates of non-believed memories are higher than the false memory rates obtained prior to the second debriefing, when participants were simply asked to report whether they had a memory for each news story.…”
Section: Discussionsupporting
confidence: 87%
“…It has previously been suggested that many reports of false memory in the literature may in fact reflect false beliefinstances where the participant believes that the event in question took place, but does not have a clear memory of it [47,48]. Recent evidence has suggested that memory and belief may have discriminable effects on subsequent behavioural intentions; for example, participants who were given a false suggestion that they had previously become ill after eating a certain food are more likely to change their behaviour if they believe the false information than if they simply remember it [16,49]-the difference being recalling a memory of the event and actually believing that it truly took place. This can be ameliorated during data collection by explicitly distinguishing between memories and beliefs, for example by asking participants to indicate whether they clearly remember seeing or hearing about the event, or simply believe that it happened (e.g.…”
Section: Memory Vs Beliefmentioning
confidence: 99%
“…Recently, in addition to the content of people's memories, there is growing interest in examining memory from a metacognitive perspective. For example, researchers have expressed interest in people's beliefs about their recollections (e.g., nonbelieved memory [NBM], Mazzoni et al, 2010; Otgaar et al, 2014) and its influence on subsequent decision‐making (e.g., Wang et al, 2019; for a mega‐analysis on belief's effect on attitude and behavior, see Bernstein et al, 2015). One way how recollections of an event can be modified is due to memory distrust.…”
Section: Introductionmentioning
confidence: 99%